2019
DOI: 10.1159/000497166
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profile and Quality of Life of Patients with Alopecia Areata

Abstract: Alopecia areata (AA) is a nonscarring alopecia with an autoimmune etiology, unpredictable course, multiple presentations, and variable psychological distress. We conducted a cross-sectional study which included 126 patients with AA. A complete medical history was documented using the Severity Alopecia Tool (SALT) to assess the severity of the disease, and the following questionnaires were applied to the participants: the Dermatology Life Quality Index (DLQI), Hospital Anxiety and Depression Scale (HADS), Plutc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 24 publications
4
80
1
Order By: Relevance
“…Like these studies, we also found higher prevalence of depression (66.7%) and anxiety (73.3%) in our patients. Comparable were the findings in another study where either depression or anxiety was present in 65.9% of adults with AA [ 17 ]. However, unlike our findings, Karia et al had reported very low anxiety (4%) and depression (18%) in AA patients [ 18 ].…”
Section: Discussionsupporting
confidence: 65%
“…Like these studies, we also found higher prevalence of depression (66.7%) and anxiety (73.3%) in our patients. Comparable were the findings in another study where either depression or anxiety was present in 65.9% of adults with AA [ 17 ]. However, unlike our findings, Karia et al had reported very low anxiety (4%) and depression (18%) in AA patients [ 18 ].…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the DLQI is a 10‐item questionnaire to measure QoL related to skin health, covering the following aspects: life, symptoms, feelings, leisure activities, work, personal relationships, and treatment 27 . DLQI is a tool easy to apply, and it has been validated in Mexican patients with diverse skin 31‐33 . Interestingly, IQoL‐32 and DLQI show a positive correlation (rs = 0.68) and could present similar results 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Patient orientation about clinical and treatment features of AA could improve adherence to treatment and prognosis [14]. Besides, we have reported that depression, anxiety, and suicide affect the quality of life and prognosis of patients with AA [15]. We propose that a good orientation, treatment adaptability according to patients’ occupations, and listening to their requirements in dermatologic consultation could increase the probability to reach remission.…”
Section: Discussionmentioning
confidence: 99%